FUEL CHARACTERIZATION ON DIESEL ENGINE - Wardan Suyanto; Budi Tri Siswanto; Muhkamad Wakid (Jurnal Penelitian Saintek, 2015)
This study aims to know the characteristics of: (1) fuel consumption on four stroke diesel engine in terms of the fuel injection timing variation in application of biosolar and Pertamina Dex, (2) emission opacity on four stroke diesel engine in terms of the fuel injection timing variation in application of biosolar and Pertamina Dex. This study used experimental approaches on four strokes single cylinder direct injection diesel engine with 4200 watts on maximum power. The engine speed and load were controlled by electricity load of electric AC generator. Observation was used to collect the data. The data was analyzed with mean calculation and showed with tables and graphics.The result of this study showed that: (1) the most efﬁ cient of fuel consumption is reached when injection timing in 30 before TDC (advanced) with biosolar, while in retreated condition is more uneconomical, (2) the least emission opacity is reached when injection timing in 30 O before TDC (advanced) with Pertamina Dex and worse in retreated condition.